Fenomena Pemberhalaan Agama - Parulihan Sipayung (Asosiasi Teolog Indonesia, 2014)
Religions tend to imprison God in their formulation. It is even not impossible that religions can replace God. The very act of replacing God is known as the idolatry of religion. Let God be God and religions be God’s hands to bring liberation to the world.